2014
DOI: 10.4236/ae.2014.24025
|View full text |Cite
|
Sign up to set email alerts
|

Biology of Planococcus citri (Risso) (Hemiptera: Pseudococcidae) on Five Yam Varieties in Storage

Abstract: Yam is an important staple cash crop, which constitutes 53% of total root and tuber consumption in West Africa. It is a cheap source of carbohydrate in the diets of millions of people worldwide and in tropical West Africa. However, attack by Planococcus citri results in shriveling of the tubers, making them become light and unpalatable. They also lose their market value. The total number of eggs laid, incubation period, developmental period and adult longevity of P. citri on stored yam Disocorea species were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 7 publications
2
7
0
Order By: Relevance
“…There was no significant difference among the mean duration of P. citri second nymphal instar of female on pumpkin fruits and potato sprouts. This result is in agreement with that of Asiedu et al (2014) who studied the biology of P. citri on five yam varieties (Disocorea species) and reported that there was no significant difference between the duration of the second nymphal instar female bred on D. rotundata var. Muchumudu and D. alata var.…”
Section: Nympal Instarssupporting
confidence: 92%
See 1 more Smart Citation
“…There was no significant difference among the mean duration of P. citri second nymphal instar of female on pumpkin fruits and potato sprouts. This result is in agreement with that of Asiedu et al (2014) who studied the biology of P. citri on five yam varieties (Disocorea species) and reported that there was no significant difference between the duration of the second nymphal instar female bred on D. rotundata var. Muchumudu and D. alata var.…”
Section: Nympal Instarssupporting
confidence: 92%
“…There was no significant difference between the mean duration of male longevity period on pumpkin fruits and potato sprouts. This result was confirmed by the findings of Asiedu et al (2014) who studied the biology of P. citri on five yam varieties (Disocorea species) and reported that adult male lived for two to four days after the final nymphal molt.…”
Section: Male Longevitysupporting
confidence: 75%
“…Information on D + S formulae was not always readily available and their components were not completely described, indicating only generically the type of compound (no chemical names given) or giving the range of the total surfactant content, but not precise figures. In fact, in many scientific publications reporting on the topic, there are no details on the specific inert ingredients or the surfactants (considered the active ingredients), or their respective proportions [47,48]. 1 Not an exhaustive web search, thus, the characteristics were not found for all products; some of them can have different commercial names elsewhere.…”
Section: Detergents and Soaps Used For Pest Control In Agriculturementioning
confidence: 99%
“…Only a few dominant ecotypes are widely grown because farmers increase the cultivation of few selected landraces that mature early, especially in those areas where yam production is expanding (Tamiru et al, 2008). Yam is a crop of major economic and cultural importance in sub-Saharan Africa (FAO, 2004) Yam is an important West African crop accounting for about 50% of root consumption and is an inexpensive source of carbohydrate (Asiedu et al, 2014). Nigeria is the leading world producer (Okigbo, 2004) and accounts for about 95% of global production, the so-called yam belt of West and Central Africa being the principal area of production (Coursey, 1967;Hahn et al, 1987).…”
Section: Introductionmentioning
confidence: 99%